New Mn2-based Heusler compounds - Kreiner, Guido; Kalache, Adel; Hausdorf, Steffen; Alijani, Vajiheh; Qian, Jin-Feng; Shan, Guangcun; Burkhardt, Ulrich; Ouardi, Siham; Felser, Claudia (Zeitschrift für Anorganische und Allgemeine Chemie, 2014)
Mn2-based Heusler compounds have attracted a great deal of interest as half-metallic ferri- and ferromagnets and as materials for spintronic applications. In this paper, we report the synthesis, crystal structure, and disorder type of the new Heusler compounds Mn2RuGe, Mn2RhGa, and the redetermination of the crystal structure of Mn 2RuSn. They crystallize cubic with L21b structure type in Fm3m, which is an inverse Heusler structure with a transition metal disorder of the type (Mn0.5,Y0.5)2MnZ (Y = Ru or Rh and Z = Ge, Ga or Sn). It is shown that an inverse Heusler structure can generally gain stability through the configurational part of the entropy of mixing at elevated temperatures without loosing too much enthalpy in the configurational part of the enthalpy of mixing owing to a special bond arrangement in the inverse type structure. The enthalpy of formation of transition-metal-based Heusler compounds and Al, Ga, and Ge as the main group metals obtained from DFT calculations and experimental data are used to confirm Burch's rule, which predicts the stability of transition-metal-based inverse Heusler compounds. Alloying tendencies as manifested in binary phase diagrams and the enthalpies obtained from the Miedema model are correlated with the stability of Heusler compounds. Burch's rule is in excellent agreement with the current available experimental data. The DFT data and general alloying tendencies show that deviations are expected from this rule. Miedema's model allows the estimation of the enthalpy of formation for the transition- and main group metal-based Heusler compounds, except for those having period 6 elements and Pd. Copyright © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Heusler compounds; Intermetallic phases; Manganese; Miedema model; Phase stability